Respuesta :
Given :
[tex] \boxed{ \rm \frac{y}{m} + \frac{y}{n} = p}[/tex]
[tex] \\ \\ [/tex]
To find:
[tex] \\ [/tex]
- Value of y
[tex] \\ \\ [/tex]
Step by step expansion:
[tex] \dashrightarrow \sf\dfrac{y}{m} + \dfrac{y}{n} = p[/tex]
write the equation
[tex] \\ \\ [/tex]
[tex] \dashrightarrow \sf \dfrac{\frac{y \times mn}{m} + \frac{y \times mn}{n}}{mn} = p[/tex]
Add y/n with y/n and we will get Lcm as mn
[tex] \\ \\ [/tex]
[tex] \dashrightarrow \sf \dfrac{\frac{y \times \cancel mn}{\cancel m} + \frac{y \times m\cancel n}{\cancel n}}{mn} = p[/tex]
Cancel the similar terms
[tex] \\ \\ [/tex]
[tex] \dashrightarrow \sf \dfrac{\frac{y \times n}{1} + \frac{y \times m}{1}}{mn} = p[/tex]
[tex] \\ \\ [/tex]
[tex] \dashrightarrow \sf \dfrac{yn + ym}{mn} = p[/tex]
remove 1 as denominator
[tex] \\ \\ [/tex]
[tex] \dashrightarrow \sf \dfrac{y(n + m)}{mn} = p[/tex]
take y as common
[tex] \\ \\ [/tex]
[tex] \dashrightarrow \sf \dfrac{(n + m)}{mn} = \dfrac{p}{y} [/tex]
transfer y to other side as denominator of p
[tex] \\ \\ [/tex]
[tex] \dashrightarrow \sf \dfrac{mn}{(n + m)} = \dfrac{y}{p} [/tex]
reciprocal the whole equation
[tex] \\ \\ [/tex]
[tex] \dashrightarrow \sf \dfrac{mnp}{(n + m)} = \dfrac{y}{1} [/tex]
transfer p other side as numerator
[tex] \\ \\ [/tex]
[tex] \dashrightarrow \boxed{ \bf y = \dfrac{mnp}{(n + m)} }[/tex]
[tex] \\ \\ [/tex]
[tex] \therefore \red {\underline {\textbf{\textsf{Option 2 i.e \{y= mnp/(m+n) \} is correct }}}}[/tex]
The value of y from the given expression is y = mnp/n+m
Subject of formula
Given the following expression
y/m + y/n = p
We are to make y the subject of the formula
yn+ym/mn = p
yn + ym = mnp
y(n+m) = mnp
Divide both sides by n+m
y(n+m)/nmp = mnp/n+m
y = mnp/n+m
Hence the value of y from the given expression is y = mnp/n+m
Learn more on subject of formula here: https://brainly.com/question/657646